Computer visualization of body motion in the constant gravitational field of the Earth - Mukushev, B.A. (Recent Contributions to Physics, 2024)
The paper analyzes computer visualization of the motion of a material point or body in a constant gravitational field. Using the MathCAD application program package, the trajectories of the body motion are constructed. Mechanical parameters of the obtained trajectories are analyzed by means of MathCAD package. A comparative analysis of physical parameters of trajectories obtained on the basis of qualitative analysis and by means of computer visualization has been carried out. Computer programs made with the help of MathCAD allowed to obtain the following results: the trajectories of thrown bodies at different angles to the horizon were drawn when their velocities were the same; the trajectories of motion of a thrown body at an angle to the horizon were found without taking into account air resistance and with taking into account viscosity of the medium; an animation of motion of a material point in two-dimensional space was created. At computer visualization a visual demonstration of internal interrelations of kinematic parameters of motion of a material point near the Earth was achieved. It is proved that the trajectories of body motion constructed with the help of computer visualization can be a method of rechecking the solution and answer of the problem on kinematics. Results of simulation modeling and regularities of body motion in two-dimensional space are presented.